The Effect of Lavender Aromatherapy on Dysmenorrhea in Adolescents - Kiki Natassia; Mahanani Mulyaningrum (Jurnal Profesi Bidan Indonesia, 2021)
Background: Dysmenorrhea is pain during menstruation, usually with cramping and centered in the lower abdomen. Handling that is often used to reduce pain is in the form of pharmacological treatment and non-pharmacological therapy, one of which is distraction relaxation, warm compresses, and aromatherapy. The mechanism of aromatherapy in the human body takes place through two physiological systems, namely the body's circulation and the olfactory system, fragrances can affect a person's mental condition, memory, and emotions. One of the aromatherapy that can be used is lavender aromatherapy. Lavender aromatherapy can provide calm, a sense of comfort, a sense of confidence, reduce stress, reduce pain, unbalanced emotions, panic, lavender can reduce pain and can provide relaxation. Purpose: to determine the effect of lavender aromatherapy on dysmenorrhea in adolescents. Method: this research is a quasi-experimental research (quasi-experimental) using the reserved non-equivalent control group design method with pre-test and post-test with accidental sampling technique, namely by taking cases or respondents who happen to exist or are available. The sample in this study were 16 respondents. Results: the results of the hypothesis test obtained a p value = 0.007 because it is less than 0.05 then Ho is rejected and Ha is accepted, meaning that there is an effect of the dysmenorrhea scale before and after being given jasmine aromatherapy treatment on dysmenorrhea. Conclusion: the results of the research above can be concluded that there is an effect of lavender aromatherapy on dysmenorrhea in adolescents in Grobogan District, Grobogan Regency